Picture inclusion! : snapshots of successful diverse classrooms - Rapp, Whitney H.; Arndt, Katrina L.; Hildenbrand, Susan M. (Paul H. Brookes Publishing Co., 2019)
This book provides educators with the theoretical foundations and practical strategies they need to create meaningful lessons for, and support all students within, a fully inclusive general education classroom. It features detailed descriptions of three sample classrooms (Grades 1, 3, and 5), each including In-depth profiles of 20 students that reflect the diversity of today's general-education classrooms Eight sample lesson plans teaching grade-level content in core subjects and specials Dozens of effective inclusive practices, adaptable for any classroom, to support individual students and g.